Successful management of refractory bleeding in liver failure with tranexamic acid: Case report and literature review. Issue 3 (26th April 2019) - Kodali, Saranya; Holmes, Chris E.; Tipirneni, Eswar; Cahill, Christina R.; Goodwin, Andrew J.; Cushman, Mary
Abstract: Essentials Uncontrolled clot breakdown with active bleeding can be seen in advanced cirrhosis. A literature review found little information on optimal management. We report a case of successful treatment with tranexamic acid for persistent subdural hematoma in this setting. A 50‐year‐old woman with advanced cirrhosis presented with spontaneous subdural hematoma. She had a worsening clinical course following craniotomy despite administration of multiple blood products. With elevation in D‐dimer, persistently low fibrinogen and poor response to factor/fibrinogen replacement therapies, we had a suspicion for uncontrolled fibrinolysis. A literature review was conducted on treatment of hyperfibrinolysis in cirrhosis, finding 4 reports in which antifibrinolytics were used to control bleeding with different outcomes. The dose of tranexamic acid used in our patient was employed from previous experience in trauma patients. We transitioned from intravenous to oral administration based on expected pharmacokinetics. Our patient had a successful outcome with resolution of bleeding.